Rogue wave - Donnelly, Jennifer (2015)
As Serafina uncovers more clues about the talismans, Neela ventures into a sea dragon's nest, and Ling learns the identity of their foe
Sequel to: Deep blue
"This edition is available for distribution only through the school market"--Page [4], cover
10 +
Accelerated reader AR
Keywords: Mermaids -- Juvenile fiction; Paranormal fiction -- Juvenile fiction; Magic -- Juvenile fiction; Good and evil -- Juvenile fiction; Paranormal fiction